2014
DOI: 10.2337/db13-1598
|View full text |Cite
|
Sign up to set email alerts
|

Acute Administration of Unacylated Ghrelin Has No Effect on Basal or Stimulated Insulin Secretion in Healthy Humans

Abstract: Unacylated ghrelin (UAG) is the predominant ghrelin isoform in the circulation. Despite its inability to activate the classical ghrelin receptor, preclinical studies suggest that UAG may promote β-cell function. We hypothesized that UAG would oppose the effects of acylated ghrelin (AG) on insulin secretion and glucose tolerance. AG (1 µg/kg/h), UAG (4 µg/kg/h), combined AG+UAG, or saline were infused to 17 healthy subjects (9 men and 8 women) on four occasions in randomized order. Ghrelin was infused for 30 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
36
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 44 publications
7
36
1
1
Order By: Relevance
“…We have recently shown that a 210-min continuous infusion of AG or co-infusion of AG and dAG to healthy subjects yielded a decreased acute insulin response to glucose and i.v. glucose tolerance, whereas dAG infusion alone did not alter these parameters (70). However, the lack of effect of dAG on glucose metabolism is not universally observed.…”
Section: Gluco-regulatory Action Of Dag In Humansmentioning
confidence: 80%
“…We have recently shown that a 210-min continuous infusion of AG or co-infusion of AG and dAG to healthy subjects yielded a decreased acute insulin response to glucose and i.v. glucose tolerance, whereas dAG infusion alone did not alter these parameters (70). However, the lack of effect of dAG on glucose metabolism is not universally observed.…”
Section: Gluco-regulatory Action Of Dag In Humansmentioning
confidence: 80%
“…In the current issue, Tong et al (19) investigated the effects of bolus followed by continuous, 210-min intravenous infusions of pharmacologic AG and UAG doses (1 and 4 mg/kg/h, respectively) on circulating insulin in healthy volunteers under fasting and intravenous glucosestimulated conditions. The key findings of the study are negative, as the inhibitory effect of AG on plasma insulin following intravenous glucose was unaffected by concomitant UAG infusion.…”
mentioning
confidence: 99%
“…Moreover, AG-UAG interactions should be systematically investigated in clinical conditions characterized by insulin resistance, when a decline in circulating UAG and higher AG-UAG ratios have been reported (3,4,8). Under these conditions, potential differential modulation by AG and UAG of additional regulators of insulin secretion should be also considered, including autonomic nervous signaling (13), circulating hormones such as growth hormone and cortisol (1,6,19), and dietary carbohydrate intake as shown by Tong et al (19). Finally, the well-demonstrated positive impact of both AG and UAG on b-cell survival and proliferation, leading to enhanced b-cell mass and higher circulating insulin in streptozotocin-induced type 1 diabetes models (10,20), poses important questions; longer-term interactions between altered insulin release and beneficial changes in b-cell mass should be directly investigated during longterm modification of ghrelin profile.…”
mentioning
confidence: 99%
See 2 more Smart Citations